Some conditions for cyclic chief factors of finite groups - Gao, B.; Miao, L.; Tang, J. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
A subgroup H of a finite group G is called -supplemented in G if there exists a subgroup B of G such that G = HB and H_1B is a proper subgroup of G for every maximal subgroup H_1 of H. The main purpose of the paper is to study the influence of -supplemented subgroups on the cyclic chief factors of finite groups.